Regulation of Juvenile Delinquency Under the Triple Values of Punishment, Rehabilitation, and Prevention (Journal of humanities and social sciences exploratio, 2026)
In recent years, there have been frequent cases of serious violent crimes committed by young minors, and the public expects the law to provide effective management and regulation. However, traditional normative mechanisms struggle to balance values such as punishment and education. Therefore, this paper briefly analyzes the construction of an integrated legal system for minors with Chinese characteristics based on the tripartite values of "punishment, reform, and prevention," aiming to flexibly address the ever-changing situation of juvenile crime. At the legislative level concerning the age of criminal responsibility, it is proposed to establish a multi-tiered, categorized criminal responsibility age system, appropriately introduce a malicious age-completion system, and implement strict conditions, procedures, and hierarchical constraints. At the level of implementation and educational reform, innovative measures such as establishing specialized judicial correctional institutions, weekend and evening sentencing, and a points-based rehabilitation system are recommended to balance the punishment and protection of juvenile offenders. In terms of prevention, effective measures include the Family Education Promotion Law, school and social education, regulation of online environments, and a tiered intervention and handling system for delinquent minors.
Keywords: Chinese characteristics; Juvenile justice; Age of criminal responsibility; Juvenile delinquency；Malicious age completion